2015
DOI: 10.1371/journal.pone.0119025
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Induces a Hyporeactivity of the Autonomic Nervous System in Response to Acute Mental Stressor and Impairs Cognitive Performance in Business Executives

Abstract: The present study examined the incidence of chronic stress in business executives (109 subjects: 75 male and 34 female) and its relationship with cortisol levels, cognitive performance, and autonomic nervous system (ANS) reactivity after an acute mental stressor. Blood samples were collected from the subjects to measure cortisol concentration. After the sample collection, the subjects completed the Lipp Inventory of Stress Symptoms for Adults and the Stroop Color-Word Test to evaluate stress and cognitive perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 84 publications
1
35
0
4
Order By: Relevance
“…It was obvious that the increase in saAA was more affected by psychological distress than physical overload. Furthermore, conflicting results from previous studies [27,28] complicate inference and highlight the importance of further studies on saAA alterations for humans suffering from chronic stress. Also, Thoma et al [29] have found that daily mean saAA values of subjects suffering from the post-traumatic stress disorder (PTSD) do not differ from the control group, while the awakening samples are significantly lower for subjects with PTSD.…”
Section: Discussionmentioning
confidence: 97%
“…It was obvious that the increase in saAA was more affected by psychological distress than physical overload. Furthermore, conflicting results from previous studies [27,28] complicate inference and highlight the importance of further studies on saAA alterations for humans suffering from chronic stress. Also, Thoma et al [29] have found that daily mean saAA values of subjects suffering from the post-traumatic stress disorder (PTSD) do not differ from the control group, while the awakening samples are significantly lower for subjects with PTSD.…”
Section: Discussionmentioning
confidence: 97%
“…A more recent study showed a similar association between chronic stress and blunting of the acute autonomic stress response in men that was not seen in women (Teixeira et al . ). Although work‐related chronic stress has been associated with lower cortisol responses to acute stress (Bellingrath & Kudielka, ), we are not aware of any prior studies that have examined sex differences in this association.…”
Section: Discussionmentioning
confidence: 97%
“…These findings would indicate increased sympathetic activity and decreased parasympathetic activity during the practice period, however, these changes were slight compared to mental state changes. Teixeira et al, reported hyporeactivity of the autonomic nervous system to acute mental stress (Stroop test) in male subjects with chronic psychological stress along with impaired cognitive performance [13]. I reported delayed recovery from acute mental stress in females with gastrointestinal symptoms who would possibly have more or less chronic stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…doi: 10.7243/2055-3447-3-1 were examined in subjects under persistent psychosocial stress in the real world in some previous articles, but the results were not enough to predict pre-disease stressed state [12][13][14].…”
mentioning
confidence: 99%